Analisis efisiensi boiler CFB 2x60 MW PLTU PT X unit 2 dengan metode direct dan indirect - Rasworo, Panji (Journal of New Energies and Manufacturing, 2022)
Steam Power Plant has one of the main components, namely the Boiler. Boiler is a machine that functions to convert water into steam. The boiler used by PLTU PT X uses a CFB type boiler. When the boiler works to convert water into steam, it is identified that heat loss occurs and when the site test uses the calorific value of coal it is different from the design so that it affects the efficiency of the boiler. The purpose of this study is to determine the heat loss that can affect the performance of the boiler and get a more efficient boiler performance. The method used in this study is a direct and indirect method where the method uses the steam property software or steam table and The Sugar Engineers Psychrometric calculation. The standard for calculating boiler efficiency used is ASME PTC 4.1 Power Test Code Steam Generator Units. The results of this study indicate that the boiler efficiency with the direct method is 81.68% at the site test and 83.85% at the design time. design so that the use during the Design conditions is more efficient than during the site test conditions and it is observed based on the two tests that the largest heat loss that can affect the performance of the boiler working efficiency is to convert water into steam, namely moisture in fuel.